Programmed death-1 inhibition increases vaccine-induced T-cell infiltration in patients with prostate cancer - Colin Pritchard; Renee N Donahue; Jeffrey Schlom; James L Gulley; Ravi A Madan; Fatima Karzai; Amy Hankin; Jennifer L Marté; Ismail Baris Turkbey; Yo-Ting Tsai; Manuk Manukyan; Moniquea Williams; et al. (Journal for ImmunoTherapy of Cancer, 2025)
Background Prostate cancer (PC) is the most frequently diagnosed cancer in men worldwide, making up 21% of all cancer cases. Although generally slow-growing, 370,000 men die from PC yearly. Immune checkpoint inhibitors (ICIs) are currently only indicated for the rare cases of microsatellite instability high or tumor mutation burden high disease. Combination therapy strategies that induce immune responses may expand the utility of ICIs. Here, we investigated the safety and efficacy of PROSTVAC, a therapeutic cancer vaccine that targets prostate-specific antigen (PSA), in combination with the programmed cell death protein-1 inhibitor nivolumab (NCT02933255).Methods We enrolled two cohorts in this trial (phase 1 and 2), both treated with PROSTVAC vaccine and nivolumab. The lead-in cohort had 12 patients with metastatic castration-resistant PC (mCRPC); the neoadjuvant cohort included 12 patients with localized PC who were candidates for radical prostatectomy (RP). We assessed tumor-infiltrating lymphocytes and programmed death-ligand 1 expression in matched formalin-fixed paraffin-embedded samples from baseline biopsies and RP samples. We measured changes in peripheral blood serum analytes, immune cell subsets and antigen-specific T cells targeting PSA, brachyury, and MUC-1 in both cohorts.Results In the lead-in cohort, two patients had a prolonged complete radiographic response by Response Evaluation Criteria in Solid Tumors V.1.1. In the neoadjuvant cohort, CD4+ T helper cell and CD8+ T-cell densities were increased by >2-fold in RP samples compared with baseline in most patients (91% and 83% of patients, respectively). Proliferation of CD4+ and CD8+ T cells also increased in RP samples compared with baseline. Most patients from both cohorts (lead-in and neoadjuvant) had a >2-fold increase in PSA-specific (82% and 58%), MUC-1-specific (64% and 73%), and brachyury-specific (70% and 82%) T cells after therapy. In peripheral blood, we detected increases in proliferative CD4+ and CD8+ T cells but reductions in total CD4+ and CD8+ T cells.Conclusion Neoadjuvant PROSTVAC in combination with nivolumab is associated with increased intratumoral T-cell infiltrates, increased circulating tumor-associated antigen-specific T cells, and with radiographic and biochemical responses in the mCRPC setting. Our findings support the idea that the addition of a vaccine to a tumor-associated antigen might improve the clinical activity of immune checkpoint inhibition.Trial registration number NCT02933255.